The Triumph of Large-Scale Agriculture and Its Socioeconomic Impact - Schlett, András; Beke, Judit (Sociologija. Mintis ir veiksmas, 2018)
Large-scale farming that utilizes industrial methods to intensify production is becoming more significant worldwide. This study explores this phenomenon and sheds light on its consequences. Contingency factors serve as key drivers when determining the advantages and disadvantages of both large-scale and small-scale farming. Significant shifts in agro-production methods have fundamentally altered ownership and production structures in agriculture and had a disastrous impact on the livelihoods of people living in rural areas.
Keywords: large-scale agriculture; labor organization; green revolution; land grabbing